Really Jazzy Jars : Glorious Gift Ideas - Browning, Marie (New York Sterling Pub., 2005)
Marie Browning's best-selling Jazzy Jars delighted crafters with its clever, yet wonderfully easy, suggestions for turning the humble jar into a breathtaking gift package. The creative fun continues in this follow-up collection, which has dozens of all-new, even better projects, patterns, techniques, and ideas. There are spectacular options galore: decorative painting with permanent enamel glass paints, decoupage, altered art, polymer clay, gluing and embellishing with trims or found objects, quick and easy lid decorations, special tags and labels, and much more. Fill up that empty jar, and make it complete, with an entire section of recipes for layered mixes and other foods. Tie a bow around the finished jar, and voila! The perfect present to make anyone happy
Include Color Illustration and Index
Keywords: Storage jars -- Decoration and ornament -- Handicraft